2008
DOI: 10.1159/000179901
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Localisation and Functional Implications of the Transporter Protein PEPT2 in the Upper Respiratory Tract

Abstract: Infectious diseases of the upper respiratory tract are widespread and may initiate exacerbations of chronic respiratory diseases such as bronchial asthma or chronic obstructive pulmonary disease. Nebulisation of antibiotics as a topic treatment may lead to high local drug concentrations. To provide data on drug transport, the present study analysed a specific drug transport system on the molecular and functional level. Messenger RNA of the proton-coupled transporter PEPT2 that mediates physiological transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…The expression of PEPT2 transporters in the human nasal cells was in agreement with the published studies reported for the rat nasal epithelium. 23 This study provided the first documented evidence that peptide transporters are expressed in the human nasal epithelium. Based on the location of PEPT1 and PEPT2 transporters on the brush boarder regions of the epithelium and their involvement in the uptake and transport of Ala-Lys-AMCA and β-alanyl-L-histidine these transporters can potentially act as surrogate carriers for drug molecules.…”
Section: ' Conclusionmentioning
confidence: 82%
See 1 more Smart Citation
“…The expression of PEPT2 transporters in the human nasal cells was in agreement with the published studies reported for the rat nasal epithelium. 23 This study provided the first documented evidence that peptide transporters are expressed in the human nasal epithelium. Based on the location of PEPT1 and PEPT2 transporters on the brush boarder regions of the epithelium and their involvement in the uptake and transport of Ala-Lys-AMCA and β-alanyl-L-histidine these transporters can potentially act as surrogate carriers for drug molecules.…”
Section: ' Conclusionmentioning
confidence: 82%
“…As these compounds are small peptides that are subject to break down to dipeptides, oligopeptides and amino acids, it is possible that the observed concentration-dependency and saturation were due to active transport by peptide transporters in the bovine nasal epithelium. Recently, Quarcoo et al 23 showed that PEPT2 transporters are expressed in the rat nasal epithelium. The purpose of this study was to provide functional and molecular evidence supporting the existence of peptide transporters in the human nasal epithelium for drug targeting.…”
Section: Articlementioning
confidence: 99%
“…Pept2 mRNA is expressed in specific cell types of the brain, including astrocytes, subependymal cells, and ependymal cells, and Pept2 protein is detected along the apical membrane of epithelial cells of the choroid plexus (Table 5) (Berger and Hediger, 1999;Shu et al, 2002). Pept2/PEPT2 mRNA and/or protein are also expressed in the enteric nervous system, colon, liver, pancreas, lungs, nasal mucosa, and mammary glands (Groneberg et al, 2001(Groneberg et al, , 2002Zhang et al, 2004a;Bahadduri et al, 2005;Ruhl et al, 2005;Lu and Klaassen, 2006;Quarcoo et al, 2009).…”
mentioning
confidence: 99%
“…PHT1 and PHT2 transporters are expressed in human intestinal segments [75,76]. Recently, it was found that PEPT2 transporters are expressed in the rat nasal mucosa epithelium and olfactory bulb [77,78]. The evidence of POT expression in the human nasal epithelium was provided by our group in 2011.…”
Section: Potmentioning
confidence: 99%
“…This has already been attempted with acyclovir [135]. [76] PEPT2 SLC15A2 Rats Nasal and olfactory mucosa [77,78] Humans Nasal epithelium [76] PhT1 SLC15A3 Humans Nasal epithelium [76] Dopamine active transporter DAT SLC6A3 Bovines Nasal and olfactory mucosa [80,85] Mice Olfactory mucosa [84] Amino acid transporter LAT-2 SLC7A8 Humans Nasal epithelium [92] Bovines Nasal and olfactory mucosa [95] Organic anion transporters OAT1 SLC22A6 Mice Olfactory epithelium [96,102] OAT6 SLC22A20 Mice Olfactory epithelium [96,102] OATP3 SLCO1A5 Rats Olfactory nerve bundles and epithelium [56] Mice Olfactory epithelium [109] Organic cation transporters OCT1 SLC22A1 Bovines Olfactory mucosa [85] Murines Olfactory mucosa [96] Humans Nasal epithelium [116] OCT2 SLC22A2 Bovines Olfactory mucosa [85] Murines Olfactory mucosa [96] Humans Nasal epithelium [116] OCT3 SLC22A3 Humans Nasal epithelium [116] OCTN1 SLC22A4 Humans Nasal epithelium [116] OCTN2 SLC22A5 Humans Nasal epithelium [116] Metal transporters DMT1 SLC11A2 Rats Olfactory epithelium [122] ZnT1 SLC30A1 Mice Nasal and olfactory epithelium [123] Nucleoside transporters ENT1 SLC29A1 Rats Nasal and olfactory epithelium [56] ENT2 SLC29A2 Rats Nasal and olfactory epithelium [56] Excitatory amino acid transporter/glutamate transporter EAAT2/GLT1 SLC1A2 Mice Olfactory epithelium [130] Humans Olfactory epithelium [130] Glucose transporter GLUT1 SLC2A1 Rats Olfactory mucosa [132] Key Term…”
Section: Strategies To Target Nasal Drug Transporters For Systemic Cmentioning
confidence: 99%